المراجعة الخارجية وفق المعايير الدولية للمراجعة - خنفري, خيضر (جامعة الوادي - University of Eloued, 2017)
إن معايير المراجعة الدولية تمكن الدول من تحقيق التوافق وتوحيد الرؤى والأهداف وتعزيز الثقة بين المهنيين، وللمعايير مزايا عديدة كدعم الثقة من طرف مستعملي هذه المعايير في مجال الاقتصاد والمساعدة في جعل هذه المهنة مستقلة، كما تساهم في إرشاد من يزاول المهنة وتمكين من تقييم أعماله المؤداة ودرجة جودتها، كما توفر تصورا لمستخدمي القوائم المالية شرطا أن تكون مناسبة ومقبولة ومتعارف عليها وحتى تتحقق لهذه المعايير المزاياا لمرجوة منها، فإنه يلزم إعادة النظر فيها من حينل لأخر وإخضاعها للتحسين والتطوير، لغرض مسايرتها للظروف المستجدة منجهة ومعالجتها للقصور والثغرات من جهة أخرى. The international auditing standards will enable States to harmonize and unify the visions and objectives and to promote trust between professionals, and the criteria many advantages as a support confidence by users of these standards in the field of economy and help make independent of the profession, and contribute to the guidance of practicing the profession and enable the evaluation of his work performed and the degree of quality also provides a vision for users of the consolidated financial condition to be suitable and acceptable and recognized on her and even achieved these standards benefits desired it is necessary to review them from time to last for improvement and development in order to bring them in line for the new conditions on the one hand and addressed the shortcomings and gaps on the other.
External audit in accordance with international auditing standards
مقال
Keywords: المراجعة الخارجية، المعايير الدولية للمراجعة، القوائم المالية; External audit,the International Standards on AuditingFinancial Statements